2021
DOI: 10.3389/fmed.2021.617659
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 in Wuhan From the Perspective of Cold-Dampness: Clinical Evidences and Mechanisms

Abstract: Traditional Chinese medicine (TCM) has played a significant role in the treatment of coronavirus disease 2019 (COVID-19) in Wuhan City. During the epidemic, Academician Tong Xiaolin suggested a close association of COVID-19 with cold-dampness, an etiological factor in TCM, by summarizing the characteristics of the COVID-19 patients in Wuhan. and the theory of Cold-dampness Plague was proposed. Based on the Cold-dampness Plague theory, a series of TCM drugs, such as Huoxiang Zhengqi Dropping Pills, Lianhua Qing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Traditional Chinese medicine (TCM) has a history of more than 2,000 years in prevention and treatment of epidemics and plagues ( Ren et al, 2020 ). By the systemic diagnosis from TCM experts, it has been generally believed that COVID-19 is a pestilence in view of its epidemic and infectious nature, characterized with the external evils such as toxin evil, wet evil, and cold evil ( Zheng et al, 2021 ), and therefore, COVID-19 is classified as “wet toxin pestilence.”…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has a history of more than 2,000 years in prevention and treatment of epidemics and plagues ( Ren et al, 2020 ). By the systemic diagnosis from TCM experts, it has been generally believed that COVID-19 is a pestilence in view of its epidemic and infectious nature, characterized with the external evils such as toxin evil, wet evil, and cold evil ( Zheng et al, 2021 ), and therefore, COVID-19 is classified as “wet toxin pestilence.”…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are a large number of COVID-19 patients, more than 93 million confirmed infections. No matter in the COVID-19 infection stage or recovery stage, many high-quality studies had shown that the effect of traditional Chinese medicine is significant, and now there is a complete evidence chain [ 153 , 154 ] about the prevention, treatment and recovery period of traditional Chinese medicine for COVID-19 [ 153 , 154 ], that is, the role of traditional Chinese medicine is self-evident, and there are a large number of patients in recovery period in many regions, so more patients need to participate in the use of traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…"Three formulas and three medicines" is a representative regimen of TCM for the treatment of COVID-19, including QingfeiPaidu Decoction (QFPD), Huashi Baidu Decoction (HSBD), Xuanfei Baidu Decoction (XFBD), Jinhua Qinggan Granules (JHQG), LHQW, and Xue Bi Jing Injection (XBJ). Many meta-analyses and clinical studies have shown that they can reduce SARS-CoV-2 virus infection by binding to ACE2, not only reducing virus-induced endothelial dysfunction, but also regulating the inflammatory immune response of immune cells, such as macrophages, and reducing systemic multiple organ injury caused by COVID-19 safely and effectively [129] , [130] , [131] , [132] , [133] , [134] . Many studies have found that these six drugs can significantly and effectively shorten the course of disease and rapidly relieve clinical symptoms in patients with mild to moderate disease, and Li et al also found that quadruple therapy with Lianhua Qingwen Capsules, ribavirin, lopinavir, and amifepristone combination can maximize the inhibition of viral infection and replication and can be used as the treatment of choice for patients with severe COVID-19 [ 135 , 136 ].…”
Section: Treatment Strategies For Covid-19 Using Western and Traditio...mentioning
confidence: 99%